Interaksi Antarwilayah dan Sebaran Covid-19 di Provinsi Kalimantan Barat - Syaiful Muazir; L Lestari; Muhammad Ridha Alhamdani; Muhammad Nurhamsyah (Department of Urban and Regional Planning, Diponegoro University, 2021)
Covid-19 is a disease that attacks the respiratory tract that began to be identified in Wuhan, China. WHO then announced the condition as a pandemic that quickly spread throughout the world. The rapid spread of the Coronavirus Pandemic (COVID-19) also occurred in West Kalimantan, Indonesia. In a spatial-temporal perspective, the spread of infectious diseases can be happened by the interconnectivity or interaction between areas, populations, and transportation facilities that facilitate community mobility. This research aims to describe the interactions between regions in West Kalimantan and the relation to the spread of the Covid-19 pandemic. The method used centrality measurement and cluster analysis, where the results of these calculations are then described in line with the distribution of the Covid-19 case in West Kalimantan. From the justification, areas with high centrality in the network configuration tend to have the most confirmed cases compared to other areas. The character of these areas tends to be the main entrance (air/port), the provincial capital, and the hub area in West Kalimantan, which is also included as the same cluster. Another interesting finding is that areas with low centrality, and included in the same cluster, have several people under surveillance which is quite large compared to the previous cluster. These areas tend to have a dense population and are directly related to the Provincial Capital and neighboring countries (border).